Posted by **Kat** on Thursday, September 24, 2009 at 3:10pm.

Rewrite the equation so that y is the fucntion of x:

a. 1/7(49-7y)=5x-3y+14

b. 4(2x-3y)=-5(x+3y)

## Answer this Question

## Related Questions

- Algebra I - Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=...
- math - Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=5x-3y+...
- algebra - How do I rewrite this equation using radicals instead of rational ...
- algebra 116 - Rewrite the equation y = 5x – 2 as a function of x. This problem ...
- math - rewrite each equation as afunction of x.-3y+4y=11 Where are the equations...
- Algebra 1A - Solve for the missing piece of the equation and rewrite the ...
- algebra - How do I tell if (x-4)/-3=y is a function? thanks It tells you wnat y ...
- algebra - Rewrite the equation 2x-3y=-6 A) f(x)=2/3x+2 b) f(x)=3/2x-3 c) f(x)=3/...
- algebra 1 - rewrite the equation so that y is a function of x. 2x = -3y + 10
- Algebra 1 - Rewrite the equation y = –3x + 5 as a function of x.